UV Induced Skin Immunosuppression - Amerio, Paolo; Carbone, Angelo; Auriemma, Matteo; Varrati, Stefano; Tulli, Antonello (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2009)
It is well estabilished that ultraviolet radiations from sunlight are carcinogenetic for skin cells. These radiations at different wavelength induce damage in the skin manly through two mechanisms : direct DNA alteration and alteration of the immune system. The skin immune system is composed by a complex network of cells and soluble mediators that help to maintain the homeostasis of the skin. UV induced immunosuppression is mediated through different photoreceptors present in the skin that lead to either: the production of immunosuppressive cytokines such as IL-10, TNF-α and TGF-β or the development of suppressive T regulatory cells or to the migration in the skin of CD11+ leukocytes in the skin that ultimately lead to the suppression of immune responses. The aim of this short review is to summarize the general knowledge in the field of UV-induced immunosuppression. The knowledge of the exact mechanism involved in this mechanism is important in order to develop strategies aimed at reducing skin cancer induction.
Keywords: immunology